(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
It was studied a floristic richness, ecological structure and coenotic diversity of macrophytes in NNP "Pyryatynsky". There are identified 34 species of macrophytes, which form 16 groups of rank association of eco-floristic classification. Analysis of overgrown rivers and flood waters showed preservation of their natural structure, a wide variety of habitats and a poverty of species richness as evidence of anthropogenic transformation of ecosystems with significant downstream. The dominance of species of eutrophic swamps complex in some areas considered as the threat of increasing waterlogging processes and transformation of habitats. It is allocated rare component of flora, confirmed the feasibility of establishing the object of protected areas of Ukraine of national importance at this area. It is recommended to expand the list of regionally rare species.